PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO WEBHOST PADA MATERI SISTEM PENCERNAAN MANUSIA SISWA KELAS V MIS NURUL HUDA KLANGON - Nadia Istiati; Rifqi Aulia Erlangga (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
The purpose of this research and development is to determine the need for developing webhost on the human digestive system material, to describe the form of webhost on the human digestive system material and effectiveness of student learning outcomes cognitively in the human digestive system material at MIS Nurul Huda Klangon. This type of research is a Research and Development (R D) research using the ADDIE model with Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques using questionnaires, and tests. The limited-scale test was carried out in class VA with 15 students and the broad-scale test was carried out in class V with 31 students. The data analysis technique used normality test, homogeneity test, Anova test, t test and gain test. The results of the study indicate that: (1) The need for webhost is needed for students to improve student learning outcomes. (2) The development of webhost based on expert validation, media validation and teachers. For material experts with a percentage of 93.75% the category is very feasible, for media experts it is 89.23% very feasible category media development webhost are very effective in influencing students' cognitive learning outcomes which are indicated by increasing students' cognitive learning outcomes with the normality test showing that student learning outcomes are normally distributed with evidence that  for pretest 0.001 0.050 and 0.151 at the post test. The homogeneity test showed that = 0.248 0.005, which means that the learning outcomes have a homogeneous variance. The ANOVA table shows that there is a significant difference in student learning outcomes (F = 12.105, p 0.05), which explains that the data are homogeneous. For the results of the average difference (t test) shows that that is = 0.00 0.005 so it is rejected and accepted, which explains that there are differences in students' cognitive learning outcomes. Gain test shows that the limit is 0.3 g 0.7, with a difference between the pre test and post test of 13.23. Gain value of 0.422 is included in the medium criteria.